37 Quantitative evaluation of lymph-vascular space invasion (LVSI) in patients affected by endometrial cancer: prognostic and clinical implications. (13th November 2020) - Restaino, S; Tortorella, L; Perrone, E; Monterossi, G; Gioè, A; Capasso, I; La Fera, E; Dinoi, G; Scambia, G; Fanfani, F; Zannoni, G; Chiantera, V
Abstract : Objectives: Lymph-vascular space invasion (LVSI) is associated with an increased risk of recurrence. Usually, the interpretation of LVSI is just qualitative, as presence or absence. The aim of this study is to examine the quantitative analysis of LVSI. Methods: Retrospective multicentre study. It included 2300 consecutive patients who received a histologically confirmed diagnosis of endometrial cancer between January 2000 and December 2018 at the Gynaecologic Oncology Unit of two tertiary hospitals in Italy. Results: The rate of lymph node metastasis increased from the 5% in patients with no LVSI, to 15% in patients with focal LVSI and 33% in those with diffuse LVSI (p < 0.001). There is a progressive increase of prognostic impact of focal and diffuse LVSI on the risk of node metastasis (AOR = 2.12, 95% CI 1.19, 3.79 for focal LVSI and AOR = 3.67, 95% CI 2.30, 5.86). Distant recurrences were more frequent in patients with diffuse LVSI compared with no LVSI (24.9% vs 6.6% respectively, p < 0.001). We found that adjuvant treatments, specifically adjuvant radiations, were associated with improved OS and DFS (median DFS = 19 months vs 97 months respectively for no adjuvant and radiation therapy, p < 0.001) in patients with diffuse LVSI. Conclusion: The presence of diffuse LVSI is an independent risk factor of both lymph node metastasis and distant recurrence in endometrial cancer patients. It is associated with decreased OS and DFS. Adjuvant radiation improved survival regardless of grading, histotype, and lymph nodal metastasis in women with diffuse LVSI.